CHALLENGES OF PONDOK EDUCATIONAL INSTITUTION AND IT’S IMPACT ON STUDENTS DEVELOPMENT - Ramiaida Darmi; Mohd Muzhafar Idrus; Hazlina Abdullah; Maziahtusima Ishak; Adibah Sulaiman; Hayati Ismail; Zulkiple Abd Ghani; Noornajihan Jaafar; Siti Rugayah Hj Tibek; Amir Husin Mohd Nor; Setiyawan Gunardi; Noor Azizi Ismail; et al. (Journal of Islamic, Social, Economics and Development, 2017)
: The pondok educational system is an institution of Islamic religion that exists and isrecognized by the community. It plays a role in spreading religious knowledge and forming aperfect Muslim personality. The Islamic education applied in the study is one of the mostimportant channels to shape character and thinking in parallel with Islamic values. Lack ofunderstanding of Islamic teaching will lead a person to behavior that is contrary to Islam.Hence, the purpose of this study is to identify the challenges faced by the pondok educationinstitution as well as to study the impact of students following the curriculum system tothemselves. This study uses qualitative and quantitative methods through document analysisand interviews via round table discussions with the authority individuals and distribution ofquestionnaire. A total of 233 respondents were selected from several pondok in PeninsularMalaysia. The findings show that there are three main factors that challenge the developmentof the present cottage curriculum, management and the recognition of cottage studies. Thefindings also found that students acknowledged that this education system had a positive impacton themselves (mean 4.59). They also acknowledged that this education system benefited theirfamilies and their environment. In conclusion, pondok education system seeks to create betterstudent orientation and produce quality students.